Zinner Syndrome: The Diagnosis and Management of a Rare Urogenital Malformation - Lucinda Lau; Kishan S. Patel; Frank Santisi; Rebecca Germaine; Sunil Jeph (Case Reports in Radiology)
This case highlights an atypical but important consideration in young males presenting with persistent gastrointestinal and/or genitourinary symptoms. Zinner syndrome (ZS) develops from embryologic maldevelopment of the distal mesonephric duct, resulting in ejaculatory duct atresia with consequent obstruction of the seminal vesicle and concomitant ureteral bud malformation, leading to renal agenesis/dysplasia. The lack of distinct clinical symptoms makes ZS a difficult diagnosis to reach: Abdominal pain and dysuria are often mistaken for prostatitis or cystitis. However, the use of modern imaging modalities aids in establishing the diagnosis. Early identification of ZS may delay progression to infertility as the duct obstruction may not be as extensive, though further research is needed to establish this connection.